PENGARUH GOOD CORPORATE GOVERNANCE (GCG) TERHADAP KINERJA KEUANGAN (ROA) PADA PERUSAHAAN SEKTOR KONSUMEN PRIMER - Sifa Indra Oktaviyani; Ela Widasari; Imas Fatimah (The Asia Pacific Journal Of Management Studies, 2023)
Financial performance is an effort made by a company to measure the success of a company in generating profits, so that it can see the growth and potential for good development of the company by relying on existing resources. This study aims to determine the effect of Good Corporate Governance on the financial performance of primary consumer sector companies listed on the Indonesia Stock Exchange in 2017- 2021. The proxies used for Good Corporate Governance are institutional ownership, the board of directors and the audit committee. Measurement of financial performance using Return On Assets (ROA). The method used in this research is by using quantitative methods. The results of the study partially show that there is an effect of the board of directors on financial performance, while institutional ownership and audit committee variables have no effect on financial performance. As for the simultaneous test, there is a significant effect between institutional ownership, the board of directors and the audit committee on financial performance.